2015
DOI: 10.1037/neu0000129
|View full text |Cite
|
Sign up to set email alerts
|

Early life instruction in foreign language and music and incidence of mild cognitive impairment.

Abstract: Objective To test the hypothesis that foreign language and music instruction in early life are associated with lower incidence of mild cognitive impairment (MCI) and slower rate of cognitive decline in old age. Method At enrollment in a longitudinal cohort study, 964 older persons without cognitive impairment estimated years of foreign language and music instruction by age 18. Annually thereafter they completed clinical evaluations that included cognitive testing and clinical classification of MCI. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 74 publications
9
85
1
Order By: Relevance
“…Major depression (Jorm, 2001; Ownby et al, 2006; Byers & Yaffe, 2011) and higher level of depressive symptoms (Wilson, Barnes, et al, 2002; Saczynski et al, 2010; Barnes et al, 2012) are each associated with higher risk of dementia, but neither major depression in the present analyses nor level of depressive symptoms in previous analyses (Wilson et al, 2014) were related to postmortem markers of AD and other late-life dementias. This suggests that depression, whether defined diagnostically or psychometrically, somehow reduces cognitive reserve and that effective treatment of depression may bolster cognitive reserve.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Major depression (Jorm, 2001; Ownby et al, 2006; Byers & Yaffe, 2011) and higher level of depressive symptoms (Wilson, Barnes, et al, 2002; Saczynski et al, 2010; Barnes et al, 2012) are each associated with higher risk of dementia, but neither major depression in the present analyses nor level of depressive symptoms in previous analyses (Wilson et al, 2014) were related to postmortem markers of AD and other late-life dementias. This suggests that depression, whether defined diagnostically or psychometrically, somehow reduces cognitive reserve and that effective treatment of depression may bolster cognitive reserve.…”
Section: Discussioncontrasting
confidence: 75%
“…Raw scores on the individual tests of cognitive function were converted to z scores, using the baseline means and standard deviations of all persons in the parent studies. The z scores were then averaged to create a composite measure of global cognition, as previously described (Wilson, Beckett, et al, 2002; Wilson, Boyle, et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…We included 13 of 1154 articles, reporting 13 separate studies fulfilling our criteria. Four studies were excluded after the full paper was retrieved -one because there was no record of whether or not participants spoke more than one language, [14], another because it did not include a monolingual comparator group [21] and two because they compared bilingual participants with multilingual rather than monolingual participants [12;13]. Of the included studies, five were prospective and reported in Table 1 and eight were retrospective or cross-sectional and are reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…While some researchers do not support this potential consequence of bilingualism when the characteristics of the samples are carefully controlled for (see Chertkow et al, 2010;Lawton et al, 2015), others report significant results even in carefully matched groups (see Alladi et al, 2013;Woumans et al, 2015). However, as correctly stated by Paap et al (2015b), the most compelling pieces of evidence at this regard may come from longitudinal studies following cohorts of individuals, and most of these studies yielded non-significant differences, or even monolingualfavoring trends (e.g., Crane et al, 2009;Lawton et al, 2015;Sanders et al, 2012;Yeung, St. John, Menec, & Tyas, 2014;Zahodne et al, 2014), while only one presented evidence in favor of a bilingual advantage at this level of analysis (Wilson, Boyle, Yang, James, & Bennett, 2015).…”
Section: Discussionmentioning
confidence: 96%